2009
DOI: 10.1177/183693910903400303
|View full text |Cite
|
Sign up to set email alerts
|

Parent and Staff Expectations for Continuity of Home Practices in the Child Care Setting for Families with Diverse Cultural Backgrounds

Abstract: DEVELOPMEnt in yOunG children is influenced not only by biological factors but also by experiences related to the child's ecological environment, such as the relationship with the primary caregiver as well as social, cultural and socioeconomic influences (Bronfenbrenner, 1979; Owen, Ware & Barfoot, 2000). Culture and society are strong determinants in the development of the individual, particularly because they affect child-rearing practices (Harkness, 1980; Vygotsky, 1978). This article focuses on two routine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The most cited skills by the parents were child care and communication skills. According to (De Gioia, 2009), these two skills are essential for cultural continuity of care giving practices. At the same time, teachers need to pay attention to the cognitive, socio-emotional and physical development of the children (Kariuki et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The most cited skills by the parents were child care and communication skills. According to (De Gioia, 2009), these two skills are essential for cultural continuity of care giving practices. At the same time, teachers need to pay attention to the cognitive, socio-emotional and physical development of the children (Kariuki et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…While a linguistic mismatch is reported in 16 of the 26 reviewed studies, the LM parents and ECEC professionals shared a linguistic and cultural background in the remaining ten. The latter studies point to smooth and open communication between the parents and professionals, which inevitably improves the relationship (Adair, 2016;Baker and Páez, 2018;De Gioia, 2009;De Gioia, 2015;Fehrer and Tognozzi, 2017;Harji et al, 2017;Gilliard et al, 2007;Loveridge et al, 2012;Mancilla-Martinez and Lesaux, 2014;Mitchell et al, 2015).…”
Section: Language Background (Mis)matchmentioning
confidence: 99%
“…teachers, educators) form stereotypes along ethnic lines regarding family cultural practices (Archer & Francis, 2007;Sanagavarapu, 2010). Other studies have found that teachers and staff assume that mainstream dominant practices are (Fleer & Hedegaard, 2010) and ignore individual family practices, simply responding to their own macro-cultural practices (De Gioia, 2009).…”
Section: School Values and Practicesmentioning
confidence: 99%
“…Recent studies on early childhood have recognised the importance of a mutual understanding between school and family, especially in increasingly multicultural societies (De Gioia, 2009;Sanagavarapu, 2010;Vuckovic, 2008). Better mutual understanding can enhance homeschool relations, as well as act for the betterment of the child.…”
Section: Introductionmentioning
confidence: 99%